Chinese multinationals: Threat to, or opportunity for, trade unions? The case of Sinohydro in Ghana - Glynne Williams; Steve Davies; Julius Lamptey; Jonathan Tetteh (International Labour Organization (ILO), 2017)
There is a growing literature on global Chinese companies, but this tends to be at a very general level. There is little research to date on the effect of Chinese involvement on workers and their unions. Although focussed on one company, SINOHYDRO, this paper addresses questions of importance to construction unions globally: What is the impact of growing Chinese MNC involvement and how should unions respond? This paper puts the experience of workers at SINOHYDRO in Ghana into perspective and argues that: there is value in standardising and formalising industrial relations practices in MNCs through an International Framework Agreement; without workplace militancy and solidarity there is little chance of progress in bargaining; it is important that guidance and best practice notes on public sector contract compliance are available to unions at a local level; greater co-ordination and co-operation between the various levels of the union movement is essential; and despite their reputation for anti-union behaviour, in certain situations Chinese companies are prepared to recognise unions and enter into dialogue with workers' representatives at workplace level.
Keywords: 330; multinational enterprise; construction industry; construction worker; Chinese; labour relations; trade union role; case study; regional level; Ghana